Not from benevolence : 20 years of economic dissent - Harris, Ralph; Seldon, Arthur (London : Institute of Economic Affairs, 1977)
To commemorate the first 20 years of the Institute, Ralph Harris and Arthur Seldon compiled an account of its output of ideas expounded by 250 authors, identifying the main themes and illustrating them by summary and quotation.
Label on cover: Transatlantic Arts, Inc., Levittown, N.Y., sole distributor for the U.S.A.
Includes bibliographical references.
rpm 27/10/2017
Loans
Keywords: Economic growth; Great Britain